(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND: To date, few data are available about severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seroprevalence in young children and the role of early-life childcare arrangements in transmission of the virus. In this study, we assessed the SARS-CoV-2 seroprevalence in children less than 6 years of age in the canton of Fribourg and identified risk factors associated with seropositivity. METHODS: The COVPED study is a population-based cross-sectional study in children less than 6 years of age living in the canton of Fribourg, Switzerland, who presented to a private paediatrician or the paediatric emergency department of the Fribourg Hospital during a 9-week period between 11 January and 14 March 2021. Immunoglobulin G antibodies against SARS-CoV-2 trimeric spike protein were measured in capillary blood samples using an in-house Luminex assay. A mean fluorescence intensity ratio of above 6 was considered as positive. Metadata was collected through electronic questionnaires. Logistic regression analysis was performed to assess the risk of seropositivity and associated factors. RESULTS: A total of 871 children, with a median age of 33 months (range 6 days to 5 years 11 months) were included; 412 (47%) were female. Overall, 180 (21%, 95% confidence interval [CI] 18–24%) children were seropositive. Age as continuous variable was not associated with seropositivity risk, apart from a higher rate in children less than 3 months of age. Univariable analysis showed that female sex was associated with a lower seropositivity risk (unadjusted odds ratio [OR] 0.69, 95% CI 0.49–0.96; p = 0.03). Day-care attendance was also associated with a lower seropositivity risk (OR 0.67, 95% CI 0.47–0.95; p = 0.03), whereas all other childcare arrangements were not associated with seropositivity. No association was found between the number of children and adults present in extra-familial care and seropositivity. Multivariable analysis identified the number of household members above the age of 12 years being positive for SARS-CoV-2 as the main risk factor for seropositivity in children (adjusted odds ratio [aOR] 7.80, 95% CI 4.65–13.07; p <0.001 for one household member, aOR 22.07, 95% CI 13.49–36.11; p <0.001 for two household members and aOR 32.20, 95% CI 9.30–111.55; p <0.001 for three or more household members). CONCLUSION: The number of household members tested positive for SARS-CoV-2 (PCR test) is the main exposure risk to seropositivity for children less than 6 years of age. But the family size is not associated with an increased risk of infection. In young children, extra-familial care does not increase the risk of becoming SARS-CoV-2 seropositive, neither does the number of contacts present in extra-familial care. As adults and children will be vaccinated and new virus variants will be circulating the risk of exposure for young children will likely change and needs further monitoring.